Implementasi Aplikasi Pengolah Data Akseptor Suntik Di Puskesmas - Febrina Sari; Mustazzihim Suhaidi; Elisa Hafrida (Politeknik Negeri Cilacap, 2020)
PUSKESMAS West Dumai provides family planning injection services to acceptors who are around the Puskesmas, but Puskesmas have difficulties in collecting data and reporting of acceptors who have injected periodically or not. During this time the data collection process of the acceptors at PUSKESMAS West Dumai is managed using Ms.Excel. The purpose of this Community Partnership Program activity is to facilitate the performance of Puskesmas in managing data on acceptors, especially injecting contraceptive users, so that it is expected that Puskesmas will be easier to manage data of acceptors in the PUSKESMAS Dumai Barat Dumai City. The method used is through an approach to the head of the Puskesmas to carry out activities and technical training in using the application. Implementation and Training of Injecting Data Acceptor Application Processing run well, The Puskesmas Admin immediately feels the convenience provided by this application, for example, the Admin is easier to do the recapitulation and management of acceptor data because the data is computerized and has a database, besides the Puskesmas Admin can print the reports of injection contraception users more quickly and accurately.